THE ROLE OF THE SOCIAL-ENTREPRENEURSHIP CORPORATIONS IN KAZAKHSTAN IN THE DEVELOPMENT OF THE PUBLIC PRIVATE PARTNERSHIP MECHANISMS - A. Taubayev; B. Doskaliyeva; S. Akenov (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article describes the features of the establishment and functioning of the specialized institutions of the public-private partnership – the social-entrepreneurship corporations in Kazakhstan. Based on the study of foreign experience of the creation of similar organizations, the advantages and problems of their functioning have been determined. The social-entrepreneurship corporations of Kazakhstan have a non-profit corporation model, but their mission is to meet the challenges of gaining profit and investments for the socio-economic development of the regions. This article describes the functioning activities of the socialentrepreneurship corporation "Saryarka" of Karaganda region, the dynamics and structure of its investment portfolio and the main problems are determined in it.